Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - Chapter 11 Review Problem Set - Page 520: 53



Work Step by Step

We use the formula $(a-b)(a+b)=a^{2}-b^{2}$ with $a=-3$ and $b=7i$. Then, knowing that $i=\sqrt{-1}$, we can substitute $-1$ for $i^{2}$ to obtain: $(-3+7i)(-3-7i)$ =$(-3)^{2}-(7i)^{2}$ =$9-49i^{2}$ =$9-49(-1)$ =$9+49$ =$58$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.